The associations between gut microbiota and inflammatory skin diseases: a bi-directional two-sample Mendelian randomization study - Zhong, Yun; Wang, Fan; Meng, Xin; Zhou, Lei (Frontiers in Immunology, 2024)
Background: Accumulating evidence shows dysregulation of intestinal flora is associated with inflammatory skin diseases, specifically atopic dermatitis (AD), psoriasis (PSO), and rosacea (ROS). However, the causality is still unclear. Objectives: To study the underlying causality between gut microbiota (GM) and AD, PSO, as well as ROS, a bi-directional two sample Mendelian randomization (2SMR) analysis was conducted. Methods: We extracted summary statistics of gut microbiota, AD, PSO, and ROS from large-scale GWAS studies. In 2SMR analysis, in addition to the inverse-variance weighted as the principal method for evaluating causal association, four different methods were also used. Sensitivity analysis and reverse 2SMR study was implemented to evaluate the robustness of 2SMR results or reverse causal relationship, respectively. Results: A total of 24 specific gut microbiota species related to AD, PSO, as well as ROS were identified by the 2SMR analysis. After using the Bonferroni method for multiple testing correction, family FamilyXIII (ID: 1957) [OR = 1.28 (1.13, 1.45), p = 9.26e-05] and genus Eubacteriumfissicatenagroup (ID: 14373) [OR = 1.20 (1.09, 1.33), p = 1.65e-04]were associated with an increased risk for AD and PSO, respectively . Genus Dialister showed a negative association, suggesting a protective role against both atopic dermatitis and rosacea. Our reverse 2SMR analysis indicated no reverse causality between these inflammatory skin diseases and the identified gut microbiota. Conclusions: In summary, this study provided evidence for the causality between GM and inflammatory skin diseases. These findings suggested supplementing specific bacterial taxa may be effective therapy for AD, PSO, as well as ROS.